Novel RAF/MEK inhibitor CH5126766/VS‐6766 has efficacy in combination with eribulin for the treatment of triple‐negative breast cancer. Issue 10 (1st August 2021) - Ono, Hisako; Horinaka, Mano; Sukeno, Mamiko; Morita, Mie; Yasuda, Shusuke; Nishimoto, Emi; Konishi, Eiichi; Sakai, Toshiyuki
Abstract: Various molecular‐targeting drugs have markedly improved the treatment of patients with breast cancer. As yet, therapies for triple‐negative breast cancer are mainly cytotoxic agents. To investigate the novel therapy for triple‐negative breast cancer, we herein examined the effects of a new combination therapy comprising a RAF/MEK inhibitor CH5126766, also known as VS‐6766, which we originally discovered, and eribulin. The combination of CH5126766 and eribulin potently inhibited cell growth in the triple‐negative breast cancer cell lines tested. The underlying mechanism in the efficacy of this combination treatment in vitro and in vivo was due to enhanced apoptosis through the suppression of survivin and Bcl‐2 family proteins. We also showed the suppressed expression of programmed cell death ligand 1 (PD‐L1) in combination therapy in vivo. We found that combination therapy with eribulin and CH5126766 for triple‐negative breast cancer inhibited cell growth by apoptosis and raised a possibility that immune responses through suppression of PD‐L1 might partially contribute to inhibition of tumor growth, indicating the potential of this combination as a novel strategy for triple‐negative breast cancer. Abstract : We showed that combination therapy with eribulin and CH5126766 for triple‐negative breast cancer inhibited cell growth by apoptosis and raised a possibility that immune responses, through suppression of programmed death ligand 1, might partially contribute to inhibition of tumor growth, indicating the potential of this combination as a novel strategy for triple‐negative breast cancer.